Preliminary study of energy and cost saving potential of lighting system in teaching building - Tham, Cheong Sheng; Awang, Mariah; Abdul Rahman, Mohammad Ashraf (Pusat Penyelidikan dan Inovasi Politeknik, Jabatan Pendidikan Politeknik, 2017)
Energy consumption and potential for energy savings become more intensive in public buildings in order to improve energy performance. This study will identify the current occupancy, lighting use patterns and lighting performance in G3 Block B teaching building of University Tun Hussein Onn Malaysia. In order to determine the energy saving potential and strategies for lighting system in the building, a series of data collection will conduct to the effects of occupancy and lighting use patterns to display the lighting energy consumption and notice to the lighting energy waste of the case study building. Moreover, lighting performance of the teaching building is also been measured to identify potential of improving the usage of lighting system. Based on the experiment data obtained, there are 36% - 46% of the total hour usage of lighting system are needlessly in the unoccupied lecture rooms. The energy and cost saving potential strategies are suggested to improve the usage and efficiency of the lighting system in the teaching building towards energy conservation.